Protection from Ultraviolet Radiation during Childhood: The Parental Perspective in Bavaria - Gefeller, Olaf (Int J Environ Res Public Health, 2016)
During childhood, parents play a vital role in sun protection of their children. Their guidance is essential for avoiding excessive exposure to ultraviolet (UV) radiation, a risk factor for developing skin cancer in later life. In a population-based cross-sectional study conducted between October 2011 and February 2012, we assessed how 3281 parents implemented sun protection for their three- to six-year-old children in practice. In particular, clothing, shade-seeking behavior, wearing of sunhats and sunglasses, use of sunscreens and the amount of time spent outdoors were ascertained in two settings (beach, garden/playground). The results showed that the overall level of parental sun protection for their children in the beach setting, and to a lesser extent also in the everyday outdoor setting, is relatively high. Using sunscreens with a high sun protection factor and instructing children to wear a sunhat were very common. Lesser attention was paid to sun-protective clothing, seeking the shade and wearing sunglasses. The amount of time spent outdoors during summer days was high. Therefore, the recommendation to completely avoid sun exposure during peak UV times around noon during summertime needs to be reinforced. In addition, the observed difference in the protective behavior between the beach and an everyday outdoor setting points to the necessity to encourage better sun protection for children also in outdoor activities of daily living.